دور القيادة االدارية في تعزيز مستوى الوالء التنظيمي دراسة تحليلية آلراء عينة من األفراد العاملين في شركة هاوكاري لتجارة االدوية والمستلزمات الطبية في أربيل - رغدة لويس فرنسيس, ماجستير إدارة األعمال, مدرس مساعد; أحمد محمود الفقي, ماجستير إدارة األعمال, مدرس مساعد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The research seeks to identify the impact of administrative leadership on the level of organizational loyalty from the point of view of the personnel working in Hawkari Company, which consist in the field of distribution and marketing of pharmaceutical products in the Kurdistan region-Iraq. This study was carried out based on the descriptive analytical method by using the questionnaire as a tool to collect data from (40) individuals working in the company, and in order to analyze the data a set of statistical methods have been used to this purpose. The research found that there are good levels of administrative leadership and organizational loyalty in Hawkari Company, as well as a significant correlation between administrative leadership and organizational loyalty. Also, there is a statistically significant effect of the types of administrative leadership in the level of organizational loyalty. The most important recommendations are the need to strengthen the identity of the organization and its values in the personnel working by the managers who lead the company, as well as the need to provide incentives for employees in such a way that prevent the turnover.